Comic Books Use in Social Studies Lesson: Texas History - Ilhan, Genc Osman; Oruc, Sahin (TURKISH EDUCATION ASSOC, 2019)
Comic books are not only a type of reading material but also a useful educative source for various lessons. Based on this, this study aims to examine the effects of comic books on middle school students' motivation and academic success in social studies course. Quasi-experimental research design was used in the current study, in which 19 students were in experimental group and 20 students were in the control group. The data gathered by the motivation scale and the achievement test. The study lasted for three weeks in 2015-2016 educational year. Findings revealed that students, who were taught by the comic book, in the experimental group, reached significantly better achievement score and higher motivation than their counterparts, who were taught in traditional classroom environment.
Keywords: Comic books; Social studies; Motivation; Academic success; Instructional material; INTRINSIC MOTIVATION; STUDENT-ACHIEVEMENT; ACADEMIC-ACHIEVEMENT; ELEMENTARY-SCHOOL; SELF-EFFICACY; KNOWLEDGE; EDUCATION; BELIEFS; TOOL; LITERACY; Education & Educational Research